Câncer gástrico após gastroplastia para obesidade mórbida - Godoy,Álvaro Queiroz de (2007)
We report a case of patient in whom a gastric remnant cancer developed about five years after a gastric bypass for morbid obesity. We review the literature on gastric cancer after gastroplasty. Access of gastric remnant after gastroplasty (Fobi-Capella) prevents evaluation and treatment of its disorders.